Perceptions and Memorization Strategies of Piano Students Toward Piano Performance: A Phenomenological Study - Wilson, Elvina L.; Simanjuntak, Stella E.; Apalat, Aera Jean S.; Beratio, Nerilyn R.; De Gracia, Khristine Ruth F.; De Dios, Sheryl Ann B.; Solidum, Jewel B. (8ISC Proceedings: Arts and Education; 8ISC Proceedings: Arts and Education, 2022)
For many piano students, it has always been a challenge to memorize pieces. Most of them would admit to making mistakes and experiencing a mental block during a performance. Difficulty in memorizing may cause difficulty in playing the piano. Though some studies about this case have already been done, this research tried to look for new findings regarding the perceptions of piano students about memorization as a major element for piano performance. The study also described the memorization strategies utilized by the students. Through purposive sampling, ten piano students were selected to participate in this phenomenological study. They were also observed during their piano practices to confirm gathered data from a semi-structured interview. An interview guide was utilized to gather information which was transcribed, categorized, and thematically analyzed. The results revealed that the piano students highly preferred to memorize because it helps boost confidence, focus, and interpret the music well. It was also revealed that during practice, certain memorization strategies such as separation of hands, repetition, singing of the melody, and listening to recordings were used to perform by memory. However, the process of being able to perform by memory takes a lot of hard work and discipline. Therefore, it is recommended for students and teachers to work together in the learning and memorization process.